Services and programmes for teenage pregnancy and support for teenage mothers - Lekganyane, Glory Mmasetjana (Družboslovne razprave, 2014)
This article seeks to juxtapose the current services and programmes that deal with the prevention of teenage pregnancies and the teenage motherhood notion in South Africa and Slovenia. The paper looks at the situation in both countries and tries to detect the main problems in the two cases and therefore proposes changes on the basis of what is known about the two countries. In other words, we describe the situation, identify problems and suggest solutions. Teenage pregnancy and teenage motherhood are always viewed as inseparable and as a discourse that exists due to a variety of social and sociological variables. The notion of teenage pregnancy and teenage motherhood is assessed against related theories and scholastic (secondary) evidence. Finally, it is argued that intervention services and programmes that are linked with the life perspective of teenagers and teenage mothers yield positive results.
Keywords: Social support; Socialna opora; Teenage girls; Najstnice; Nosečnost; Pregnancy; human pregnancy; Materinstvo; Motherhood; Južnoafriška republika; South Afrika; Slovenia; Slovenija